2022
DOI: 10.1371/journal.pone.0262318
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of patients with MDR-TB and its determinants at referral hospitals in Ethiopia

Abstract: Background There is limited empirical evidence in Ethiopia on the determinants of treatment outcomes of patients with multidrug-resistant tuberculosis (MDR-TB) who were enrolled to second-line anti-tuberculosis drugs. Thus, this study investigated the determinants of treatment outcomes in patients with MDR-TB at referral hospitals in Ethiopia. Design and methods This study was underpinned by a cross-sectional quantitative research design that guided both data collection and analysis. Data is collected using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
1
11
0
2
Order By: Relevance
“…The overall favorable treatment outcome was 66.30%. This is comparable with the study conducted in Ethiopia ( 19 ). The study revealed that Khat chewing, baseline smear result greater than 2+, poor anti-TB adherence and bilateral lung cavity had a significant association with unfavorable DR-TB treatment outcome.…”
Section: Discussionsupporting
confidence: 90%
“…The overall favorable treatment outcome was 66.30%. This is comparable with the study conducted in Ethiopia ( 19 ). The study revealed that Khat chewing, baseline smear result greater than 2+, poor anti-TB adherence and bilateral lung cavity had a significant association with unfavorable DR-TB treatment outcome.…”
Section: Discussionsupporting
confidence: 90%
“…A study conducted from a teaching and referral hospital in Wolayta Sodo, Ethiopia, reported similar findings. 39 However, studies in Ethiopia and abroad reported that undernutrition, 31 , 33 HIV infection, 21 , 26 and history of anti-TB drug use 40 were risk factors for unsuccessful treatment outcomes such as treatment failure and death. In the present study, there were a considerable number of patients with unknown HIV and BMI status, which may have underestimated the frequency of HIV infection and BMI, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Six covariates (w1 to w6) including age, time to reach health facility, number of times stop tuberculosis treatment, gender, education level, and contact with MDR-TB were determined. Other confounders of the MDR-TB include HIV [ 14 ], malnutrition, and comorbidities [ 15 ]. We assumed that history of previous TB treatment was independent from the occurrence of MDR-TB while controlling for other confounders (w) to achieve conditional exchangeability between exposure and outcome.…”
Section: Methodsmentioning
confidence: 99%